GRUPUGE Perspective: Endoscopic Ultrasound-Guided Drainage of Peripancreatic Collections - Pereira,Flávio (2021)
Abstract: Pancreatic and peripancreatic collections (PPC) are a known complication of acute pancreatitis. They are categorized into four types of collection: (1) acute peripancreatic fluid collection, (2) pseudocyst, (3) acute necrotic collection and (4) walled-off necrosis. Most PPC resolve spontaneously or are persistent but asymptomatic. Intervention is needed in a minority of patients with infected or symptomatic collection. Endoscopic ultrasound-guided transmural drainage is currently the first-line treatment option for PPC management. It has shown great technical and clinical success, similar to percutaneous or surgical approaches, but with lower morbidity and costs and better quality of life. In this review article, the GRUPUGE presents an updated perspective on the potential role of endoscopic ultrasound-guided drainage of peripancreatic collections, addressing the selection criteria and the technical issues of different techniques and analysing emerging data on their efficacy and safety.